Device associated healthcare associated infection (DA-HAI): a detailed analysis of risk factors and outcomes in a university hospital in Rome, Italy - Luca Guarente; Claudia Mosconi; Mariagrazia Cicala; Carolina De Santo; Fausto Ciccacci; Mariachiara Carestia; Leonardo Emberti Gialloreti; Leonardo Palombi; Giuseppe Quintavalle; Daniele Di Giovanni; Ersilia Buonomo; Stefania Moramarco; et al. (Elsevier, 2024)
Summary: Introduction: This study investigates the impact of invasive procedures on healthcare-associated infections (HAI) at Policlinico Universitario Tor Vergata in Rome, Italy, aiming to understand their role in device-associated HAI and to inform prevention strategies. Methods: A retrospective cohort analysis was conducted, examining mandatory discharge records and microbiology data from 2018 across all departments. The study focused on adult patients, analysing the correlation between invasive procedures and HAI through univariate and multivariate logistic regression. Results: Of the 12,066 patients reviewed, 1,214 (10.1%) experienced HAI. Univariate analysis indicated an association between invasive procedures and HAI (OR = 1.81, P < 0.001), which was not observed in multivariable analysis. Specific procedures significantly raised HAI risks: temporary tracheostomy (AOR = 22.69, P <0.001), central venous pressure monitoring (AOR = 6.74, P <0.001) prolonged invasive mechanical ventilation (AOR = 4.44, P <0.001), and venous catheterisation (AOR = 1.58, P <0.05). Aggregated high-risk procedures had an increased likelihood of HAI in multivariable analysis (OR = 2.51, P < 0.001). High-risk departments were also notably associated with HAI (OR = 6.13, P < 0.001). Conclusions: This study suggests that specific invasive procedures, such as temporary tracheostomy, significantly increase HAI risks. The results highlighting the need for targeted infection prevention and control procedures and supports the need for innovative methods such as record-linkage in policymaking to address HAI. These findings inform clinical practice and healthcare policy to improve patient safety and care quality.